A comprehensive review on lotus seeds (Nelumbo nucifera Gaertn.): Nutritional composition, health-related bioactive properties, and industrial applications. (February 2022) - Punia Bangar, Sneh; Dunno, Kyle; Kumar, Manoj; Mostafa, Hussein; Maqsood, Sajid
Graphical abstract: Highlights: This is the first review addressing nutritional profile, bioactivities, and industrial applications of Lotus seed. Lotus seed is a rich source of lipid, protein, starch, vitamins, and minerals, and bioactive compounds. Lotus seed extracts display various bioactivities (anti-cancer, anti-diabetes, anti-microbial, anti-obesity, and neuroprotection). The application of lotus seeds as an ingredient in functional food is outlined in the review. Abstract: Lotus is a member of a small family of Nelumbonaceae and is regarded as a sacred flower grown as a freshwater aquatic plant. All plant parts are utilized as food and medicine. Lotus seed (LS) is an important part of the lotus plant due to its nutritional and bioactive components. The presence of phenolic compounds imparts numerous bioactivities to the LS extracts. Nutritional composition is considered crucial for evaluating new ingredients for food applications. Hence, the review deals with the nutritional composition of the LS and bioactivities of LS extracts, viz., anti-cancer, anti-proliferation, anti-diabetic, anti-inflammatory, neuroprotective, antioxidant, and immunomodulatory action. LS also possesses a significant amount of industrially important components which are beneficial for the formulation of food products. The overall profile of the lotus seed makes them potential nutraceutical and bioactive food ingredients. Utilizing this low-cost horticultural waste for producing value-added products is a novel step in its sustainable utilization. The article aimed to comprehensively collate some of the vital information published on lotus seeds incurred in the agri-food sector and critically discussing the potentiality of tapping bioactive compounds from lotus seeds considered as wastes and/or by-products in the entire agriculture-based food sector.